Experience of workplace incivility and its impact on stress and turnover intention among the nurses working at a hospital: Cross-sectional survey approach - Devan Kanitha; Poonam R Naik (Wolters Kluwer Medknow Publications, 2021)
Background: Incivility in the workplace drowns the mental health of the nurses and hampers the daily routine. The majority of the nurses working at hospitals were experiencing incivility. It affects the physical and psychological health of the nurses. Experience of workplace incivility and its impact on stress and turnover among nurses was discussed in this study. Materials and Methods: Cross-sectional survey approach was used to select 50 nurses by simple random sampling technique. Standard scales for incivility, stress, and pre-tested scale for the turnover intention was used to collect the data. Result: Nurses experience incivility in their workplace almost from all the sources. The majority (64%) of the staff nurses had a moderate level of stress and 30% had average intention to leave the present job. There was a positive relationship found between the experience of incivility and stress (r = 0.43, p < 0.002), stress, and turnover intention (r = 0.40, p < 0.004). Conclusions: Experience of incivility provokes stress among the nurses, and this may influence turnover intention.